Enhancing External Oversight of Constitutional Judges: A Study on the Role of the Judicial Commission in Indonesia and South Korea - Suparto Suparto; Kim Hyeonsoo; David Hardiago; Rani Fadhila Syafrinaldi (Universitas Negeri Semarang, 2024)
This study addresses the urgent need for enhanced external oversight of constitutional judges in Indonesia and South Korea, driven by increasing concerns over judicial integrity and accountability. Recent instances of judicial misconduct and rising public dissatisfaction highlight the necessity for effective mechanisms that ensure transparency and ethical conduct among judges. The research investigates the roles and effectiveness of the Judicial Commissions in both countries, providing critical insights into their operations and impacts on judicial oversight. By employing a comparative approach, the study reveals the strengths and weaknesses of each commission’s framework, focusing on ethical guidelines, disciplinary processes, and public engagement strategies. It identifies best practices that could be adapted or improved to enhance judicial oversight, thereby fostering greater public trust in the legal system. The findings indicate that while both commissions aim to uphold judicial integrity, their effectiveness is influenced by contextual factors such as political dynamics and public perception. Additionally, this study explores the implementation of external oversight for Constitutional Judges in Indonesia, particularly in light of the establishment of the Constitutional Court following the 1945 Constitution amendment. Given the court’s crucial role in upholding constitutionalism, the exclusion of constitutional judges from oversight mechanisms is untenable. The Judicial Commission emerges as the most suitable body for external supervision, yet prior legislative efforts to integrate constitutional judges under its purview have been invalidated by the Constitutional Court. To rectify this, the study recommends amending Article 24B paragraph (1) of the 1945 Constitution to explicitly include